Developing Professional Capability: Growing Capacity and Competencies to Meet Complex Workplace Demands. Issue 163 (3rd September 2019) - Melacarne, Claudio; Nicolaides, Aliki
Abstract: This paper uses the constructs of capacity and competencies to explore how transversal and vertical skills are becoming more central than in the past for adult educators and higher educational design teaching. In this chapter, the authors will describe the context where this idea was created and describe two approaches that develop transversal and vertical skills in adult educational settings.